IDEA TESTING AND ANALOGY PREDICT CREATIVITY OF BIOLOGY STUDENTS IN ONLINE LEARNING - Dem Vi Sara; Eko Yuliastuti Endah Sulistyawati; Mutimanda Dwisatyadini; Diki; Ida Malati Sadjati; Endang Indrawati (Journal of Research and Innovation In Open and Distance Learning, 2023)
Identifying factors affecting students’ success is important. This is a study on creativity of biology students to solve their learning problem. The participants are biology students at Universitas Terbuka (UT), the only single mode distance learning university in Indonesia. conducting online tutorial in introductory biology. Descriptive and bivariate correlation statistics data are collected, including one dependent variable about improvement of problem-solving skill and six independent variables. The six independent variables are problem identification, information searching, idea generation, analogy, integrating different concepts, and idea testing. Demographic data are age, gender, and length of daily online activities. There are 73 students returned the survey with 23.4% response rate. Most students (more than 60%) agree to some extent in all the variables. There are different levels of agreement about the use of online tutorial regarding gender, age and length of daily online activities. There are only two out of six independent variables that have significant correlation (0.05 significance level, two-tailed) with improvement of problem-solving skill, which are analogy and idea testing. Keywords: creativity, biology, problem-solving, distance learning, online learning